2015
DOI: 10.4102/ajod.v4i1.157
|View full text |Cite
|
Sign up to set email alerts
|

Enabling disability inclusive practices within the University of Cape Town curriculum: A case study

Abstract: BackgroundDisability inclusion in the curricula of higher education institutions contributes to socially responsive graduates with a capacity to address the cross-cutting issue of disability in development. This article discusses a study conducted at the University of Cape Town (UCT), South Africa, to explore disability inclusion.MethodologyAn instrumental case study approach was adopted and a thematic analysis of data was done.FindingsAcademic staff found a variety of ways to include disability, such as discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…"The role of [Higher Educational Institutes] is not only to provide access for students with disabilities," but also to "build knowledge of disability into all academic spheres, and to produce graduates who are able to understand and deal with disability issues in their professional lives" [159] (p. 2). Undergraduate disabled research students could be the ones building this body of knowledge.…”
Section: Knowledge Production and Its Governancementioning
confidence: 99%
“…"The role of [Higher Educational Institutes] is not only to provide access for students with disabilities," but also to "build knowledge of disability into all academic spheres, and to produce graduates who are able to understand and deal with disability issues in their professional lives" [159] (p. 2). Undergraduate disabled research students could be the ones building this body of knowledge.…”
Section: Knowledge Production and Its Governancementioning
confidence: 99%
“…A widespread effort to operationalise UDL principles is not currently being made in South Africa, as is evident from the literature on the experiences of both SWDs and lecturers, as the latter still lack appropriate skills for adapting the curriculum. For instance, one study of lecturers from the University of Cape Town by Ohajunwa et al (2015) detailed that participants who were committed to supporting SWDs in the mainstream curriculum mostly did so out of their personal interest or by their own methods, often in an ad hoc manner, because they lacked of training on how to appropriately support their SWDs. I found that most South African HEIs are not providing staff development and training on campus regarding disability, despite recent recommendations that the university management within these institutions should provide professional development programmes (Makiwane 2018).…”
Section: Lecturers' Lack Of Training In Udlmentioning
confidence: 99%
“…This study revealed that, despite the willingness on the part of some lecturers to include disability issues in undergraduate curricula, most of these participants were unsure if they were using the best methods, and the seven academic staff that included disability issues were doing so in isolation as opposed to as part of a departmental effort (Ohajunwa 2012). Lecturers sampled in a study conducted by Ohajunwa et al (2015) expressed concerns that an overcrowded curriculum presents challenges to disability inclusion in teaching and research. Such complaints could possibly be mitigated if these lecturers had received training in UDL principles, as they would employ such principles in making efforts to ensure that inclusive features have been built into classroom instruction right from the outset of designing the curriculum (Brinckerhoff et al 2002).…”
Section: Lecturers' Lack Of Training In Udlmentioning
confidence: 99%
“…The amount of resources available for SWDs perceived by academics could encourage them in providing academic support and improve upon teaching instructions to accommodate SWDs (Coleman & Shevlin, 2019). Relative absence of resources in providing institutional support for SWDs instil a sense of under-appreciation and therefore an unnecessary need to exert any effort in integrating SWDs in their respective institutions (Ohajunwa et al, 2015). Instructions in handling and meeting the various requirements of SWDs need to be established with clear guidelines on what authorised actions are to be taken and whom to inquire should questions regarding the aforementioned requirements arise (Izzo, Hertzfeld, Simmons-Reed& Aaron, 2001).…”
Section: 2relationships and Hypothesis Testing 221 Perceived Inmentioning
confidence: 99%
“…Coupling positive attitudes with the availability of appropriate support in the context of higher education institutions directly relate to the success and retention of SWDs (Rao, 2004;Ohajunwa et al, 2015). By realising the supportive efforts put forward by institutions via the development of plans, procedures, the construction of facilities and learning strategies for SWDs, the perceptions brought on by academics can be influenced (Nelson, 1990;Tinklin et al, 2004).…”
Section: Pis -Attitude Towards Swds (Atswds)mentioning
confidence: 99%